Inheritance Rights of Women in Islamic Family Law: Comparative Analysis Across Jurisdictions - Putra, Dwi Rayhan Sunandar (Journal of Islamic Family Law, 2025)
This study aims to provide a comparative analysis of women's inheritance rights under Islamic family law across various Islamic jurisdictions. A purposive sampling technique is employed, aiming to select cases and legal documents that provide comprehensive insights into the comparative aspects of the inheritance rights of women. The data analysis is conducted using thematic analysis to identify patterns, similarities, and differences in the inheritance practices, legal interpretations, and the impact of reforms. The findings suggest that the strict or flexible application of the law in the Islamic family system correlates with each jurisdiction's socio-cultural and legal environment. The study concludes that the inheritance right of women in Islamic family laws exhibits significant variation across jurisdictions, influenced by cultural, socio-economic, and legal contexts. This study suggests that jurisdictions should consider adopting flexible legal reforms, focused on judicial discretion and family agreements to create more equitable inheritance distributions for women. This research may serve as a valuable resource for legal scholars, policymakers, and activists who are engaged in advocating for gender equality within Islamic legal systems.